SETTLEMENT OF STRIP FOOTINGS ON RECENTLY DEPOSITED TROPICAL COASTAL LOWLANDS - H. B. Poorooshasb (International Association of Lowland Technology, 2001)
Many coastal lowlands are recently deposited. That is the soil layer consists of a thick layer of normally consolidated clay, silty clay, clayey silt or a combination thereof. In certain areas the deposit is so soft at the grade level that it cannor support the slightest of loads. In other areas, perhaps a few kilometers away from the shore-line, the surficial soils have become over-consolidated by desiccation and can support some load. These localities are, more often than not, of very gentle slope and carry scant vegetation. The layer supportng the crust (the desiccated soil) is still normally consolidated, highly compressible and its water content often exceeds the LL. Construction on such a formation obviously presents a serious problem and certain guidelines may be of value. It is the aim of the present paper to provide some such information. The discussions are limited to the performance of strip footing for low cost single story housing units.